Influence Capability Dynamic Capabilities and Strategic Agility to Superiority Competing in the Manufacturing Industry - Agung Dharmajaya, Muhammad (Journal of Management, 2026)
The manufacturing industries were met with an environment constantly changing and dynamic, characterized by disruptive advances in technology, customer preferences that shifted physically and an international competitive field marked by rigorous standards. From these aspects of reality, have established the fact that it is necessary not only for a firm but also the whole society to upgrade themselves and their competitive edge. The aim of this research is to provide a detailed analysis of how dynamic capabilities and strategic flexibility affect manufacturing enterprises move forward from a superior position. Both these themes will be examined in the work one by one and also together. The methodology adopted in this research was quantitative and involved the use of questionnaires to collect relevant data. The data for this study was gathered carefully by means of a questionnaire survey of people meeting certain requirements set for our purpose. The data was analyzed using multiple linear regression techniques to test each variable's influence in turn alone and together as well. The results of study showed that dynamic capabilities have a positive and significant effect on competitive superiority. What this shows is that a company in identifying opportunities, making use of those opportunities and transforming its own resources, the degree to which it is doing this will determine the quality of its competitive strength. Strategic agility was also found to have a statistically significant positive impact on competitive superiority. This means that the company's ability to make rapid adjustments of movement or attitude in order to meet changes in the market strengthens its competitive position. When taken together, both dynamic capabilities and strategic agility have a significant impact on competitive superiority. In conclusion, the integration of organizational capacityfor enhancement and strategic flexibility will be a decisive factor in maintaining the leading position over time. This study has profound practical implications, pointing out the need for manufacturing enterprises to strengthen their adaptive and responsive strategies in order to find a suitable way out of the increasingly complex, ever changing competitive environment in which they operate.